Brill's Companion to the Reception of Aristophanes - Walsh, Philip (Brill's Companions to Classical Reception Ser, 2016)
Contents -- Preface and Acknowledgements -- Notes on Contributors -- Part 1 Aristophanes, Ancient and Modern: Debates, Education, and Juxtapositions -- 1 Aristophanes in Antiquity: Reputation and Reception -- 2 Modern Theory and Aristophanes -- 3 Aristophanes, Gender, and Sexuality -- 4 Aristophanes, Education, and Performance in Modern Greece -- 5 Teaching Aristophanes in the American College Classroom -- 6 The "English Aristophanes": Fielding, Foote, and Debates over Literary Satire -- 7 Teknomajikality and the Humanimal in Aristophanes' Wasps -- 8 Branding Irony: Comedy and Crafting the Public Persona -- Part 2 Outreach: Adaptations, Translations, Scholarship, and Performances -- 9 Aristophanes in Early-Modern Fragments: Le Loyer's La Néphélococugie (1579) and Racine's Les Plaideurs (1668) -- 10 Aristophanes and the French Translations of Anne Dacier -- 11 The Verbal and the Visual: Aristophanes' Nineteenth-Century English Translators -- 12 Comedy and Tragedy in Agon(y): The 1902 Comedy Panathenaia of Andreas Nikolaras -- 13 J.T. Sheppard and the Cambridge Birds of 1903 and 1924 -- 14 Murray's Aristophanes -- 15 "Attic Salt into an Undiluted Scots": Aristophanes and the Modernism of Douglas Young -- 16 Classical Reception in Posters of Lysistrata: The Visual Debate Between Traditional and Feminist Imagery -- 17 Afterword -- General Bibliography -- Index Nominum et Rerum.